Spatial and temporal characteristics of chromophoric dissolved organic matter and its relation to light attenuation in the Singapore strait - Lim, Marcus Kian Yew (Nanyang Technological University, 2021)
Chromophoric Dissolved Organic Matter (CDOM) strongly absorbs light in the UV-blue region and may reduce light availability in the water column, especially in coastal waters where concentrations of CDOM are high due to input from terrestrial sources. Where this CDOM comes from, and how much it may affect light availability in the water column in the Singapore Strait remains to be discovered. This study proposes a remote sensing approach to observe long-term and seasonal patterns in CDOM concentrations within the Singapore Strait. Empirical algorithms for aCDOM(412), DOC, S275-295, Kd(490), total non-water absorption and euphotic depth were developed. These models produced good validation metrics and were applied to remote sensing reflectance values from the Moderate resolution Imaging Spectroradiometer MODIS ocean colour product for data within the years 2003-2019. We did not notice an increasing trend in CDOM concentrations within the years 2003-2019. Strong variation in CDOM concentrations were observed seasonally. This study suggests spatial and temporal variations in CDOM are largely due to hydrodynamic forcings influenced by the Asian monsoon, such as the reversal of current direction during the Southwest monsoon which leads to the influx of large quantities of terrigenous CDOM from the Malacca Strait during the Southwest monsoon. Strong spatial and temporal variations in S275-295 were observed. Kd(490) and euphotic depth correlated strongly with both CDOM absorption and the contribution of CDOM to non-water absorption in the western portions of the Singapore Strait